The HIV-1 Entry Process: A Stoichiometric View. Issue 12 (December 2015) - Brandenberg, Oliver F.; Magnus, Carsten; Regoes, Roland R.; Trkola, Alexandra
Abstract : HIV-1 infection starts with fusion of the viral and the host cell membranes, a process mediated by the HIV-1 envelope glycoprotein trimer. The number of trimers required to complete membrane fusion, referred to as HIV-1 entry stoichiometry, remains under debate. A precise definition of HIV-1 entry stoichiometry is important as it reflects the efficacy of the viral entry process and steers the infectivity of HIV-1 virion populations. Initial estimates suggested a unanimous entry stoichiometry across HIV-1 strains while recent findings showed that HIV-1 strains can differ in entry stoichiometry. Here, we review current analyses of HIV-1 entry stoichiometry and point out future research directions to further define the interplay between entry stoichiometry, virus entry fitness, transmission, and susceptibility to antibody neutralization. Trends: A refined understanding of the HIV entry stoichiometry emerges, indicating that most HIV-1 isolates require more than one envelope glycoprotein trimer for target cell entry. HIV-1 strains can differ in entry stoichiometry, reflecting the divergent potential of their envelope trimers to solicit energy required for the membrane fusion process. The HIV-1 entry stoichiometry is intimately linked with virus entry kinetics. The HIV-1 entry stoichiometry is a contributing factor of virus infectivity. The HIV-1 entry stoichiometry is an important parameter for the accurate determination of antibody numbers and concentrations required for virus neutralization.